Environmental problems in protected areas: Stakeholders' views with regard to two neighboring National Parks in Greece. Issue 6 (2nd September 2014) - Andrea, Veronika; Tampakis, Stilianos; Tsantopoulos, Georgios; Manolas, Evangelos
Abstract : Purpose: – The purpose of this paper is to propose an approach regarding the management measures for solving environmental problems in protected areas. Two neighboring protected areas with different features were chosen in order to investigate the similarity of the environmental problems with regard to these two areas and if it is possible for these problems to be solved through a network of protected areas. Design/methodology/approach: – The research was carried out through the use of a questionnaire which was distributed to the inhabitants and visitors of both areas, as well as through interviews with the representatives of organizations responsible for the management and administration of those areas and representatives of the municipalities and the regional authorities these two national parks belong to. Simple random sampling was applied to the inhabitants and cluster sampling to the visitors. Findings: – The results show that with regard to the visitors the most important problem is illegal hunting while for the inhabitants equally important is the problem of pollution and cleanliness. However, those responsible with the management of the two National Parks think that the greatest threat to the wider area is the problem of floods. Originality/value: – The views of the stakeholders in a given time, provides us with the best possible information for solving the problems faced and can be used as a tool for increasing the effectiveness of the measures which have been taken to deal with the particular problems.